Analisis penerapan manajemen risiko reputasi dalam meningkatkan kepercayaan nasabah bank syariah - Salsabila, Atha (Maliki Interdisciplinary Journal, 2026)
This study aims to analyze the implementation of reputational risk management in enhancing customer trust in Islamic banking. Reputation is a strategic yet vulnerable asset, particularly due to the requirement of compliance with Sharia principles. This research employs a qualitative literature review approach, examining various sources related to risk management, governance, and customer trust. The findings indicate that effective reputational risk management involves four main stages: risk identification, assessment, monitoring, and control. Its implementation is supported by the role of the Sharia Supervisory Board, the application of Good Corporate Governance (GCG), and proactive communication strategies. Factors influencing reputational risk include internal aspects such as Sharia compliance, service quality, and managerial ethics, as well as external factors such as digital media exposure and macroeconomic conditions. Case studies reveal that failure to manage reputational risk can significantly reduce customer trust and threaten banking stability. Conversely, effective management enhances customer loyalty and attracts new clients. Therefore, reputational risk management and customer trust have a reciprocal relationship, making it a crucial element in sustaining competitive advantage in Islamic banking.